Gender discrimination in the workplace: comparative legal analyses of case studies and law of Russian Federation and Kingdom of Norway - Polyakova, Anna (Riga Graduate School of Law, 2018)
The paper gives an overview of the problems of professional segregation and discrimination in labor remuneration and how countries like Norway have managed to successfully enhance gender equality. It focuses on the gender aspect conditions of the workplace, the nation’s institutional features, and the social-economic characteristics of both women and men as subjects of the workforce. Several cases concerning gender discrimination in the labor market are not recognized. This creates a gap in the existing legal system, hence, limiting the efficiency of the Labor Code of the Russian Federation and other legislative measures put in place to deal with gender discrimination.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Labour law; Gender discrimination; Russian Federation; Norway